Phylogeographic Analyses Reveal the Early Expansion and Frequent Bidirectional Cross-Border Transmissions of Non-pandemic HIV-1 Subtype B Strains in Hispaniola - Bello, Gonzalo; Arantes, Ighor; Lacoste, Vincent; Ouka, Marlene; Boncy, Jacques; Césaire, Raymond; Liautaud, Bernard; Nacher, Mathieu; Dos Santos, Georges (Frontiers in Microbiology, 2019)
The human immunodeficiency virus-type 1 (HIV-1) subtype B has probably been circulating on the island of Hispaniola since the 1960s, but information about the early viral history on this Caribbean island is scarce. In this study, we reconstruct the dissemination dynamics of early divergent non-pandemic subtype B lineages (designated BCAR) on Hispaniola by analyzing a country-balanced dataset of HIV-1 BCARpol sequences from Haiti (n = 103) and the Dominican Republic (n = 123). Phylogenetic analyses supported that BCAR strains from Haiti and the Dominican Republic were highly intermixed between each other, although the null hypothesis of completely random mixing was rejected. Bayesian phylogeographic analyses placed the ancestral BCAR virus in Haiti and the Dominican Republic with the same posterior probability support. These analyses estimate frequent viral transmissions between Haiti and the Dominican Republic since the early 1970s onwards, and the presence of local BCAR transmission networks in both countries before first AIDS cases was officially recognized. Demographic reconstructions point that the BCAR epidemic in Hispaniola grew exponentially until the 1990s. These findings support that the HIV-1 epidemics in Haiti and the Dominican Republic have been connected by a recurrent bidirectional viral flux since the initial phase, which poses a great challenge in tracing the geographic origin of the BCAR epidemic within Hispaniola using only genetic data. These data also reinforce the notion that prevention programs have successfully reduced the rate of new HIV-1 transmissions in Hispaniola since the end of the 1990s.